New neo-Clerodane Diterpenoids Isolated from Ajuga decumbens Thunb., Planted at Pingtan Island of Fujian Province with the Potent Anticancer Activity - Zacchaeus Olatunde, Olagoke; Yong, Jianping; Lu, Canzhong (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Aims: The aim of this study is to find the anticancer lead compounds or drug candidates from Chinese Traditional Plant Medicine of Ajuga decumbens Thunb. Background: Ajuga decumbens Thunb. has been used in clinical for a long time in China and was selected in “Chinses Pharmacopoeia” (part I in 1977) for its wide spectrum biological activities: such as anticancer, antioxidant, antifeedant, antibacterial, anti-inflammatory, antihyperlipidemic, anti-cholinesterase and cytotoxicity activities. However, there are relatively fewer studies of Ajuga decumbens Thunb. that have been carried out till now. For some years, our research group focused on the discovery of new anticancer agents, so we studied the chemical compositions of Ajuga decumbens Thunb., planted in Pingtan island of Fujian Province, to discover new anticancer lead compounds or candidates from this Chinese Traditional Plant Medicine. Methods: The dichloromethane (DCM) extract was obtained in this work, and then this extract was used for silica gel column chromatography to obtain different polar fractions. Several similar fractions were combined according to TLC or HPLC analysis. The combined fractions were isolated by preparative TLC or preparative HPLC to obtain the pure compounds and HPLC was used to detect the purity. All isolated compounds were determined by NMR (1HNMR, 13CNMR, DEPT, HMBC, HSQC, 1H-1H COSY and NOESY), HRESIMS and single crystal X-ray diffraction methods. The in vitro anticancer activity was evaluated using CCK8 method. Results: Seven compounds [three new compounds 1-3 and four known compounds (Ajugacumbins A, Ajugacumbin B, Ajugamarin A2 and Ajugamarin A1)] were isolated from Ajuga decumbens Thunb. in this work, and their structures were confirmed. The biological evaluation showed that 3 and Ajugamarin A1 exhibited potent in vitro anticancer activity both against A549 cell lines with IC50s=71.4 μM and 76.7 μM; and against Hela cell lines with IC50s=71.6 mM and 5.39×10-7 μM, respectively. Conclusion: Compounds (3 and Ajugamarin A1) can be regarded as the lead compounds for the development of anticancer agents.
Keywords: single crystal X-ray diffraction